Effect of energy density and virginiamycin supplementation in diets on growth performance and digestive function of finishing steers - Juan D. Navarrete; Martin F. Montano; Constantino Raymundo; Jaime Salinas-Chavira; Noemi Torrentera; Richard A. Zinn (Asian-Australasian Journal of Animal Sciences, 2017)
Objective This study was determined the influence of virginiamycin supplementation on growth-performance and characteristics of digestion of cattle with decreasing dietary net energy value of the diet for maintenance (NEm) from 2.22 to 2.10 Mcal/kg. Methods Eighty crossbred beef steers (298.2±6.3 kg) were used in a 152-d performance evaluation consisting of a 28-d adaptation period followed by a 124-d growing-finishing period. During the 124-d period steers were fed either a lesser energy dense (LED, 2.10 Mcal/kg NEm) or higher energy dense (HED, 2.22 Mcal/kg NEm) diet. Diets were fed with or without 28 mg/kg (dry matter [DM] basis) virginiamycin in a 2×2 factorial arrangement. Four Holstein steers (170.4±5.6 kg) with cannulas in the rumen (3.8 cm internal diameter) and proximal duodenum were used in 4×4 Latin square experiment to study treatment effects on characteristics of digestion. Results Neither diet energy density nor virginiamycin affected average daily gain (p>0.10). As expected, dry matter intake and gain efficiency were greater (p<0.01) for LED- than for HED-fed steers. Virginiamycin did not affect estimated net energy value of the LED diet. Virginiamycin increased estimated NE of the HED diet. During daylight hours when the temperature humidity index averaged 81.3±2.7, virginiamycin decreased (p<0.05) ruminal temperature. Virginiamycin did not influence (p>0.10) ruminal or total tract digestion. Ruminal (p = 0.02) and total tract digestion (p<0.01) of organic matter, and digestible energy (p<0.01) were greater for HED vs LED. Ruminal microbial efficiency was lower (p<0.01) for HED vs LED diets. Conclusion The positive effect of virginiamycin on growth performance of cattle is due to increased efficiency of energy utilization, as effects of virginiamycin on characteristics of digestion were not appreciable. Under conditions of high ambient temperature virginiamycin may reduce body temperature.